PENGARUH KONDISI SOSIAL TERHADAP PERILAKU PENGAMBILAN KEPUTUSAN “PEREMPUAN” PEMILIK UMKM JAWA TIMUR UNTUK MENGADOPSI E-COMMERCE - Elya Kurniawati (Jurnal Sosiologi Pendidikan Humanis, 2019)
Recent competition in the economy is dominated by companies that are able to implement the right technology into their business. E-commerce technology provides many conveniences for business people, including women as owners of Micro, Small, and Medium Enterprises (MSME) in East Java. Women are very potential and competent as actors and managers of Micro, Small, and Medium Enterprises (MSME). The purpose of this study is to determine the social conditions that influence the decision-making of these women as owners of Micro, Small, and Medium Enterprises (MSMEs) to adopt e-commerce. This study was conducted using quantitative descriptive methods. The sample consisted of 41 women as owners of MSME in East Java. Data were analyzed using percentages. The results of the study show that the majority of these MSME owners have understood e-commerce, but some of them have not adopted e-commerce as their competitive strategy